The molecular composition of soil dissolved organic matter regulated by reactive mineral-associated organic matter under a broad range of climates - Ding, Yang; Shi, Zhenqing (Applied geochemistry, 2025)
Organic matter retained by reactive minerals constitutes an essential mechanism for long-term storage of carbon in soil, a process that is governed by climate factors. However, how the reactive mineral-associated organic matter affects the composition of soil dissolved organic matter (DOM) across a broad range of climates remains unclear. In this study, the contents of reactive minerals and their associated organic matter were determined by the chemical extraction method. Moreover, the effects of organic matter retained by reactive minerals on soil DOM composition were investigated at molecular level across a wide environmental gradient, by employing Fourier transform ion cyclotron resonance mass spectrometry, solid-state 13C nuclear magnetic resonance and statistical analyses. The results of FT-ICR-MS and correlation analyses indicated that the relative abundances of carbohydrates and proteins/amino sugars decreased, while the relative abundance of condensed aromatics increased with the increase of the content of organic matter retained by reactive minerals per unit mass (i.e., (OC)RN) in soils. We highlighted that the adsorption and dissolution processes of DOM molecules, especially aromatic molecules, on reactive minerals played crucial roles in regulating the molecular composition of DOM in soil solution. Furthermore, (OC)RN was controlled by climate-driven chemical weathering (e.g., precipitation). Our results imply that (OC)RN is a key variable for regulating soil DOM composition under the impacts of climates, and can be used in developing prediction models for carbon cycling. •Soil DOM composition was regulated by reactive mineral-retained organic matter.•(OC)RN was driven by precipitation.•The abundances of carbohydrates and proteins decreased with the increase of (OC)RN.•The abundance of condensed aromatics increased with the increase of (OC)RN.